Зображувальний і виражальний аспекти наративу щоденника Докії Гуменної (Літератури світу: поетика, ментальність і духовність, 2016)
For the first time the text filling of D. Humenna’s diary, pictorial and expressive components from the standpoint narratology, section of literary studies, which object of the research is the theory of narration, have been analyzed in the article. There was an attempt to analyze the structural organization of the diary, as well as dialogical interaction of the author / reader that provides the opportunity to objectively assess the results of the creative work of the memoirist. It is proved that the author and the recipient interact in the text, the interpretations of the narrator (the diarist) and the perception of her thoughts by the recipient can be seen.
Keywords: наратор; інтерпретація; діаріуш; оповідь; рефлексивність; автор; читач